Brasil e PALOP: política externa do governo Lula da Silva 2003-2010 - Fernandes, Maelqui (2018)
The present research analyzes the actions of the Brazilian foreign policy during the governments of President Luiz Inacio Lula da Silva (2003-2010) in relation to the African States of the Official Portuguese Language, aspects to be addressed was summarized in bringing literatures and data that show the action of the Brazilian government with its African counterparts. The points that composed this work were chosen based on the importance of these in any relations between states.